Analisis Penyebab Manajemen Pendidikan Inklusi Di SMP Swasta Muhammadiyah 48 Medan - Maisa Muti Salsabila Hasibuan; Makmur Syukri (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ANALYSIS OF THE CAUSES OF INCLUSIVE EDUCATION MANAGEMENT IN MUHAMMADIYAH PRIVATE JUNIOR HIGH SCHOOL 48 MEDAN This study aims to analyze in depth the factors causing the suboptimal management of inclusive education at SMP Swasta Muhammadiyah 48 Medan, examined from the aspects of planning, organizing, actuating, and controlling. A qualitative case study approach was employed. Data were collected through in-depth interviews, field observations, and document studies involving five informants—principal, vice-principal, student affairs coordinator, and two teachers—on April 13, 2026. Thematic analysis was applied, with data validity maintained through source and technique triangulation and member checks. The results reveal that (1) planning was conducted based on student needs assessments, but constrained by budget limitations and the unavailability of specialized support staff; (2) organizing was ineffective due to the absence of certified training and systematic coordination mechanisms; (3) differentiated instruction was implemented but impeded by an unfavorable teacher-to-student ratio and the diversity of students' special needs; and (4) evaluation was routinely conducted, yet its follow-up remained suboptimal. The primary causal factors include insufficient teacher competence in inclusive education, the absence of specialized support personnel, limited facilities and funding, and the lack of integrated internal policies.